Effectiveness of PjBL-JAS-based Student Worksheets on Environmental Change Materials to Improve Students' Problem Solving Ability and Creativity - Eryka Oktaviana; Saptono, Sigit; Marianti, Aditya (Journal of Biology Education, 2025)
The change in curriculum to the Merdeka Curriculum provides a lot of changes in learning strategies, approaches, methods and models. Students need learning methods that can bring them to have the ability to be responsive to local, national and global issues and play an active role in providing problem-solving solutions. The purpose of this study was to test PjBL and JAS-based learning using student worksheets as learning tools. Students are asked to actively discuss, observe, explore and create a product. The N-Gain test results show that student worksheets are effective for improving students' problem solving skills and creativity. Problem solving ability and creativity of experimental class students are better when compared to control class students. The Mann-Whitney Test results show that there is a significant difference in value between the control class and the experimental class. Classical learning completeness of experimental class students was better than control class students.